Heart failure and palliative care: training needs assessment to guide priority learning of multiprofessionals working across different care settings. Issue 1 (March 2015) - Millerick, Yvonne; Armstrong, Iain
Abstract : Purpose of review: International bodies acknowledge that palliative care principles and access to palliative care services should be offered to persons living with and dying from advanced illness such as heart failure. Without an appropriately trained workforce, however, appropriate goals of care and associated reductions in hospital utilizations may not be feasible. Marie Curie Cancer Care, British Heart Foundation Scotland and NHS Greater Glasgow and Clyde are working in partnership to improve the quality and access to palliative care for patients and their caregivers living with and dying from advanced heart failure. A training needs assessment has been undertaken as part of this programme in order to inform the development of training specific to heart failure and palliative care. Recent findings: The results of the training needs assessment showed that the majority of respondents had some level of training needs to underpin their existing knowledge and skills in relation to palliative care, heart failure or both. Summary: Well trained professionals will improve the coordination, earlier identification, quality of care provision and communication between all stakeholders. In doing so, the opportunity to facilitate preferred care wishes and preferred place of care for patients and families is optimised. Without this aligning, clinical practice with national guidance is not feasible.